PENGARUH KOMPETENSI DOSEN TERHADAP MOTIVASI BELAJAR PADA MAHASISWA FAKULTAS PSIKOLOGI UIN “SGD” BANDUNG - Tahrir Tahrir (Psympathic : Jurnal Ilmiah Psikologi, 2013)
This research was initiated from the phenomena  that psychology students have low motivation in learning and 60% of lectures have no educational background of psychology. Causal design was used to know the effect of one variable toward others. Sample are 100 students. Hypothesis analysed using regresion statistical analysis. Result shows that regresion model based on research data is significant. Lecturer competence give a linear effect toward student learning motivation